Asuhan Keperawatan Pada Ny. S Dengan Pneumonia - Yenti, Sisri Dela Putri (Akper Kesdam I/Bukit Barisan Padang, 2025)
Pneumonia is an inflammation of the lungs known as wet lung caused by various microorganisms including: bacteria, viruses, fungi and microbacteria as well as infection in the air sacs in the alveoli. Based on data from the World Health Organization (WHO) in 2021, it is stated that pneumonia incidents claimed the lives of more than 740,180 people. Adults over 65 years of age are also at risk of developing pneumonia. The aim of this research is to apply emergency nursing care to Ny. S with pneumonia in the Sultan Syahrir ward, TK III Dr. Hospital. Reksodiwiryo Padang 2022. The research design used was descriptive with a case study design. This research was conducted for three days. The research subject in this case study was a patient with pneumonia. Data collection is used by narrating answers obtained from the results of in-depth interviews conducted to answer the problem formulation. The results of the study showed that Mr. Health problems and their prevention with disease process educational interventions. The conclusion of this research is that with the implementation given, Ny. S nursing problem was resolved and the intervention was stopped.